2009
DOI: 10.1172/jci38940
|View full text |Cite
|
Sign up to set email alerts
|

Epididymis seleno-independent glutathione peroxidase 5 maintains sperm DNA integrity in mice

Abstract: The mammalian epididymis provides sperm with an environment that promotes their maturation and protects them from external stresses. For example, it harbors an array of antioxidants, including non-conventional glutathione peroxidase 5 (GPX5), to protect them from oxidative stress. To explore the role of GPX5 in the epididymis, we generated mice that lack epididymal expression of the enzyme. Histological analyses of Gpx5 -/-epididymides and sperm cells revealed no obvious defects. Furthermore, there were no app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
191
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(212 citation statements)
references
References 54 publications
15
191
0
6
Order By: Relevance
“…HPX15 could be protecting sperm cells directly, as indicated by its secretion into the spermathecal lumen and by the presence of peroxidase activity on sperm tails, or could play a role in maintaining the correct physiology of spermathecal cells. Close association of peroxidase with sperm cells is reminiscent of the mammalian system, in which glutathione peroxidase GPX5 is secreted within the epididymis lumen, the site of sperm storage and maturation in males, and is found associated with sperm cell membranes, in which it prevents DNA damage, lipid peroxidation, and premature activation of the sperm by ROS (30,31). Downstream effects on embryogenesis caused by fertilization by partially damaged sperm may also cause or contribute to the lower fertility of dsHPX15-injected females.…”
Section: Discussionmentioning
confidence: 99%
“…HPX15 could be protecting sperm cells directly, as indicated by its secretion into the spermathecal lumen and by the presence of peroxidase activity on sperm tails, or could play a role in maintaining the correct physiology of spermathecal cells. Close association of peroxidase with sperm cells is reminiscent of the mammalian system, in which glutathione peroxidase GPX5 is secreted within the epididymis lumen, the site of sperm storage and maturation in males, and is found associated with sperm cell membranes, in which it prevents DNA damage, lipid peroxidation, and premature activation of the sperm by ROS (30,31). Downstream effects on embryogenesis caused by fertilization by partially damaged sperm may also cause or contribute to the lower fertility of dsHPX15-injected females.…”
Section: Discussionmentioning
confidence: 99%
“…28 When the latter was knocked out, the animals developed an age-related phenotype associated with the induction of oxidative DNA damage in the spermatozoa and the appearance of birth defects in the offspring. 29 In addition to such antioxidant enzymes, small molecular mass free radical scavengers are also generated in the male tract, and are major constituents of the antioxidant protection afforded to the spermatozoa by seminal plasma. The most important of these scavengers are vitamin C, uric acid, tryptophan, spermine and taurine.…”
Section: Lack Of Antioxidant Protectionmentioning
confidence: 99%
“…GPx catalyzes the reduction of organic and inorganic hydroperoxides by acting as an electron donor. The GPx family consists of several proteins classified according to their sequence, substrate specificity, and subcellular localization (Chabory et al 2009). Several studies have demonstrated the importance of the GPx family during spermatogenesis and its relationship to male factor fertility (Schneider et al 2009).…”
Section: Resultsmentioning
confidence: 99%